Waste Processing and Recycling Product Marketplace Application Using Tensorflow and Midtrans API Technology - Eko Budi Setiawan; Bayu Afriyadi (IJNMT (International Journal of New Media Technology), 2025)
Both developed and developing countries face waste problems worldwide. The recycling process can not only help reduce the amount of waste but also produce new products with economic value. In order to support this effort, information and communication technology, especially Android-based applications, can be an effective solution. This application can provide education, recommendations, and a marketplace platform for recycled products, hoping to allow the public to access information and market their products more efficiently. Previous research supports the development of this application, showing great potential in helping the community manage waste effectively and economically. This study shows that Android-based waste processing and recycled product marketplace applications have great potential in helping to overcome waste problems. The test results of the application features show that all functions work well, which is my expectation. In addition, the user acceptance test shows that the majority of respondents agree that this application is effective in reducing waste accumulation (88%), facilitating the recycling process (93.36%), and providing economic value for recycled products (89.6%). This application has become a practical solution for educating the public and increasing participation in waste management while providing economic benefits through recycling.